Reclamation Plan for Production Operation Phase of Quartz Sand Mine in Riau Islands - Dita Irwanti Pratiwi; Mohammad Nurcholis (Journal of Earth and Marine Technology (JEMT), 2023)
PT. X is a quartz sand mining company located in Riau Islands. PT. X has a mine life of 5 years, starting in the first year of 2023 until the last year of 2027. Mining activities have a negative impact on the environment, therefore reclamation activities are carried out at the production operation stage. The purpose of this study is to determine the area of land to be reclaimed, techniques and equipment to be used in reclamation, land stewardship, revegetation, maintenance, and reclamation costs. This research uses the actual calculation method this method has 4 stages, namely the preparation stage, the data collection stage, the research stage in the field, and the stage of preparing the final report. At the data collection stage using primary and secondary data owned by PT.X. Reclamation of the production operation stage carried out by PT. X uses Hybrid Coconut plants. Hybrid coconut will be reclaimed on former mining land during the life of the mine whose work process is carried out in tandem with quartz sand mining activities. The reclamation cost plan of PT. X consists of direct costs and indirect costs. The total cost plan of reclamation of PT. X amounted to Rp. 583,799,620.00.